Niobate / carbon composite material and preparation method and application thereof
By introducing the nanoporous structure of metal organic frames (MOFs) into the niobium-based oxide electrode and the MOFs-derived conductive matrix composite, the problem of poor conductivity of niobium-based oxide is solved, and the cycle stability and rate performance of lithium-ion batteries are significantly improved.
Patent Information
- Application Number
- CN202411639666.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-18
AI Technical Summary
As the negative electrode material of lithium-ion batteries, niobium-based oxides have poor electron/ion conductivity, resulting in faster energy/power density attenuation at high magnifications, limiting their large-scale applications.
By using metal organic frames (MOFs) as the precursor template, a nanoporous structure is formed by high-temperature heat treatment, the contact area between the niobium-based oxide electrode and the electrolyte is increased, and combined with the MOFs-derived conductive matrix to provide a fast electron transport channel.
It improves the cycle stability and rate performance of lithium-ion batteries, extends the cycle life of the battery, reduces the heat treatment temperature, and saves energy consumption.
Smart Images

Figure CN119774663A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a niobate / carbon composite material and a preparation method and application thereof. Background Art
[0002] With the development of new energy technologies, electric energy has been widely used as a clean energy source. Among them, lithium-ion batteries have received widespread attention due to their high-performance energy storage technology. However, in order to obtain a wider range of application markets, lithium-ion batteries require not only high capacity and energy density, but also stable cyclability, fast charge and discharge rates, and long cycle life. Niobium-based oxides are common high-rate negative electrode materials with higher theoretical capacity, better safety performance and cycle stability than graphite electrodes, and have the potential to be applied to lithium-ion batteries. However, niobium-based oxides generally have poor electronic / ionic conductivity, resulting in a rapid decay of energy / power density at high rates, limiting their large-scale application.
[0003] At present, the methods to improve the above problems are mainly the micro-nano structure design of materials and composite with conductive matrix. Micro-nano structure can shorten the diffusion path of lithium ions and electrons, thereby increasing the transmission rate of lithium ions and electrons and improving the rate performance; composite with conductive matrix can provide a fast electron transmission channel and improve the overall electronic conductivity of the electrode. Carbon materials have become the most widely used composite conductive matrix due to their high conductivity, large surface area and stable physical and chemical properties. At present, researchers often improve the electrochemical properties of niobium-based oxides by compounding them with porous carbon, graphene, carbon nanotubes and other carbon materials, but their conductive properties are still limited. In addition, the contact area between niobium-based oxide particles and electrolyte is also one of the important factors affecting its high rate performance.
[0004] Chinese patent CN 111969197A discloses a calcium-based niobate compound potassium ion battery negative electrode material with a framework structure and a preparation method thereof, using Ca2Nb2O7 of several hundred nanometers as a potassium ion battery negative electrode material, showing good cycle stability and a stable voltage platform. However, the Ca2Nb2O7 particles are solid structures, which are not conducive to the full infiltration of the electrolyte. In addition, the material is pure Ca2Nb2O7 without composite conductive materials, and its conductivity is poor, which limits its high rate performance.
[0005] Chinese patent CN 109767925A discloses a T-Nb2O5 / egg white carbon composite material for lithium ion supercapacitors and its preparation method. Niobium oxalate is used as the Nb source and egg white is used as the C source. A nitrogen-rich porous T-Nb2O5 / egg white carbon composite material can be prepared by a hydrothermal-annealing two-step method. This material can effectively alleviate the stacking and agglomeration of Nb2O5 nanoparticles, thereby increasing the effective specific surface area of the material and the utilization rate of the active material. However, in the Nb2O5 / carbon composite material obtained by adding an additional carbon source, the binding force between Nb2O5 and carbon is relatively poor, which is not conducive to long-term cycle stability. Summary of the invention
[0006] In view of the problems in the background technology, the purpose of the present invention is to solve at least one of the technical problems existing in the prior art, and to provide a niobate / carbon composite material and its preparation method and application. The present invention uses metal organic frameworks (MOFs) as precursor templates, and forms a nanoporous structure through high-temperature heat treatment to increase the contact area between the niobium-based oxide electrode and the electrolyte, providing more central sites for electrochemical reactions, and effectively speeding up the process of lithium ion insertion / extraction; the MOFs-derived conductive matrix composite can provide a fast electron transmission channel and improve the overall electronic conductivity of the electrode. At the same time, niobate is a derivative of MOFs, and has a close combination with the carbon material derived from MOFs, which is beneficial to cycle stability. In addition, MOFs has a unique controllable structure and can provide an effective template for subsequent structural design. The combination of the above strategies greatly promotes the kinetic process of niobium-based oxide electrode reactions. When the electrode material is used as a negative electrode material for lithium-ion batteries, it has a higher capacity and a longer cycle life.
[0007] The technical solution of the present invention is as follows:
[0008] The first aspect of the present invention provides a method for preparing a niobate / carbon composite material, comprising: adding terephthalic acid and a metal salt into an organic solvent A, mixing to obtain a solution A, subjecting the solution A to a solvothermal reaction to obtain a MOFs precursor powder;
[0009] The niobium salt is dissolved in an organic solvent B, the MOFs precursor powder is added, and the mixture is mixed and subjected to a solvent thermal reaction to obtain a powder α, and the powder α is heat-treated to obtain a niobate / carbon composite material.
[0010] As a preferred technical solution of the present invention, the method for preparing the niobate / carbon composite material of the present invention specifically comprises the following steps:
[0011] (1) adding terephthalic acid and a metal salt into an organic solvent A and stirring to obtain a solution A;
[0012] (2) transferring the solution A obtained in step (1) into a reactor for solvothermal reaction, followed by washing and drying to obtain MOFs precursor powder;
[0013] (3) dissolving niobium salt in organic solvent B, then adding the MOFs precursor in step (2), stirring and ultrasonicating, placing in a reactor for solvent thermal reaction, washing and drying to obtain powder α, and heat treating the powder α to obtain a niobate / carbon composite material.
[0014] In step (1), the MOFs precursor is synthesized using the following components in the following dosage ratios:
[0015] Organic solvent A 10-25ml;
[0016] Terephthalic acid 1-2mmol;
[0017] Metal salt 0.3-3.5mmol;
[0018] In step (1), the metal salt is at least one of cobalt acetate, cobalt nitrate, cobalt chloride, ferric chloride, ferric nitrate, ferric acetate, nickel acetate, nickel nitrate and nickel chloride.
[0019] In step (1), the organic solvent A is at least one of N,N-2-methylformamide, diethylformamide and dimethyl sulfoxide.
[0020] In step (1), the solution needs to be stirred for at least 5 minutes, and the stirring time is preferably 5-15 minutes.
[0021] In step (2), the solvent thermal reaction temperature and time are 100-130° C. and 15-24 hours, respectively.
[0022] In step (3), the niobate / carbon composite material is synthesized using the following components in the following dosage ratios:
[0023] Organic solvent B 25-50ml;
[0024] MOFs precursor 160-450mg;
[0025] Niobium salt 0.13-0.59mmol;
[0026] In step (3), the niobium salt is at least one of niobium oxalate, niobium acetate and niobium chloride; and the organic solvent is at least one of ethanol and N,N-2-methylformamide.
[0027] In step (3), the solution needs to be stirred and ultrasonicated for at least 10 minutes, and the stirring and ultrasonication time is preferably 10-30 minutes.
[0028] In step (3), the solvent thermal reaction temperature and time are 150-180° C. and 20-30 hours, respectively.
[0029] In step (3), the protective atmosphere for heat treatment is nitrogen or argon, and the reaction temperature and time for heat treatment are 600-900° C. and 1-3 hours, respectively.
[0030] The second aspect of the present invention provides a niobate / carbon composite material prepared by the above method. The present invention uses MOFs as a precursor, and prepares a niobate / carbon porous composite electrode by solvent heat combined with heat treatment of a niobium salt solution, and maintains a porous structure after calcination. That is, the niobate / carbon composite material prepared by the present invention is a porous structure, and the niobate belongs to the orthorhombic system.
[0031] Specifically in the present invention, the niobate is at least one of iron niobate, cobalt niobate and nickel niobate.
[0032] The third aspect of the present invention provides the use of the niobate / carbon composite material as a negative electrode material for a lithium ion battery.
[0033] As a preferred technical solution of the present invention, the obtained niobate / carbon composite material, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are made into a slurry in a mass ratio of 7:2:1 and coated on the copper current collector, and a disc with a diameter of 1.2 cm is punched out as a lithium-ion battery electrode to assemble the battery. A microporous polypropylene membrane is used as a separator and 1 molL -1 A button cell is assembled with LiPF6 as solute, ethylene carbonate (EC) and dimethyl carbonate (DMC) as solvent in a volume ratio of 1:1, and a lithium sheet negative electrode.
[0034] The assembled lithium-ion battery was placed for 12 hours and then subjected to constant current charge and discharge test with a charge and discharge voltage of 3V-0.01V. The capacity, rate performance and charge and discharge cycle performance of the lithium-ion battery negative electrode were measured in an environment of 25±1℃.
[0035] According to tests, the battery prepared by using the niobate / carbon composite material of the present invention as the negative electrode material of the lithium-ion battery has excellent cycle and rate performance.
[0036] The present invention has at least one of the following beneficial effects:
[0037] (1) First, the present invention adopts phthalic acid and metal salt solvothermal method to prepare MOFs precursor powder. MOFs precursor powder is the basis for forming carbon network. Compared with the prior art, the MOFs precursor powder prepared by the present invention has the characteristics of uniform particles and simple preparation. Secondly, the prepared MOFs precursor powder and niobium salt are subjected to solvothermal reaction to obtain powder α. The present invention adopts a simple solvothermal method to prepare niobate / carbon composite porous material. Compared with the commonly used solid phase sintering (above 1000°C) of niobate, the heat treatment temperature is reduced, energy consumption is saved, and the synthesis method is simple and effective. In addition, the niobate material prepared by the solvothermal method has more uniform morphology and more nano-sized size, which is conducive to promoting electrode reaction kinetics and improving the electrochemical performance of lithium ion batteries. Then, the powder α is heat-treated under a protective atmosphere. The present invention heat-treats the powder α at a temperature of 600-900°C for 1-3 hours to form niobate and MOFs-derived carbon. The formed niobate is a MOFs derivative and has a close combination with the MOFs-derived carbon material, thereby forming a niobate / carbon composite material with a porous structure. The applicant found in the study that the temperature and time of heat treatment are key conditions for the formation of niobate and MOFs-derived carbon. If the treatment temperature is too low, it is not conducive to the formation of high-conductivity MOFs-derived carbon; if the treatment temperature is too high, the porous structure of niobate will be destroyed, resulting in agglomeration.
[0038] (2) The introduction of MOFs in the present invention brings about structural adjustability. The structural adjustability of the precursor can effectively increase the specific surface area of niobate and construct a loose porous structure, which is conducive to the infiltration of the electrolyte. In addition, MOFs-derived carbon also provides an external electron transmission channel for iron niobate. At the same time, MOFs-derived carbon in situ encapsulates niobate, which can improve the binding force between the two phases, effectively improve the stability of the electrode structure, and at the same time slow down the agglomeration of active materials during the electrochemical cycle.
[0039] (3) Compared with the traditional niobate electrode, the niobate / carbon composite porous material prepared by the present invention presents a nanoscale microstructure, which shortens the diffusion path of lithium ions and electrons, increases the transmission rate of lithium ions and electrons, and promotes the electrochemical reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The X-ray diffraction (XRD) pattern of the iron niobate / carbon composite material prepared in Example 1;
[0041] Figure 2 (a) and (b) are scanning electron microscope (SEM) images of the precursor MOFs prepared in Example 1 at different magnifications;
[0042] Figure 3 (a) and (b) are SEM images of the iron niobate / carbon composite material prepared in Example 1 at different magnifications;
[0043] Figure 4 The battery cycle performance of the iron niobate / carbon composite electrode material prepared in Example 1;
[0044] Figure 5 This is the battery rate performance of the iron niobate / carbon composite electrode material prepared in Example 1. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below with specific examples, but the present invention is not limited to the following specific examples.
[0046] Embodiment 1:
[0047] (1) 1.2 mmol of terephthalic acid and 2.5 mmol of ferric chloride were added to 15 ml of N,N-2-methylformamide and stirred for 10 minutes to obtain solution A;
[0048] (2) The solution A obtained in step (1) was transferred to a 100 ml reactor and reacted at 110° C. for 20 hours, and then washed and dried with anhydrous ethanol to obtain a solution based on the central ion Fe 3+ MOFs precursor powder with terephthalic acid as ligand;
[0049] (3) 0.2 mmol of niobium pentachloride was dissolved in 35 ml of ethanol, and then 200 mg of the MOFs precursor in step (2) was added. After stirring and ultrasonicating for 20 minutes, the mixture was placed in a 100 ml reactor and reacted at 170° C. for 20 hours. The powder α was obtained after washing with anhydrous ethanol and drying. After heat treatment at 750° C. under nitrogen for 2 hours, a black powder was obtained, which was the iron niobate / carbon composite material.
[0050] Figure 1 This is the XRD pattern of the iron niobate / carbon composite material prepared in Example 1. Figure 1 It can be seen that the phase of the iron niobate / carbon composite material prepared in Example 1 is orthorhombic FeNb2O6 (JCPDS 72-0483). Figure 2 (a) and (b) are SEM images of the precursor MOFs at different magnifications. The precursor MOFs are uniform dodecahedral particles with a size of approximately 500 nm. Figure 3 (a) and (b) are SEM images of iron niobate / carbon composite materials at different magnifications, which have a porous structure.
[0051] Embodiment 2:
[0052] (1) 1.2 mmol of terephthalic acid and 2.5 mmol of ferric chloride were added to 15 ml of N,N-2-methylformamide and stirred for 10 minutes to obtain solution A;
[0053] (2) The solution A obtained in step (1) was transferred to a 100 ml reactor and reacted at 110° C. for 20 hours, and then washed and dried with anhydrous ethanol to obtain a solution based on the central ion Fe 3+ MOFs precursor powder with terephthalic acid as ligand;
[0054] (3) 0.13 mmol of niobium pentachloride was dissolved in 35 ml of ethanol, and then 160 mg of the MOFs precursor in step (2) was added. After stirring and ultrasonication for 20 minutes, the mixture was placed in a 100 ml reactor and reacted at 170° C. for 20 hours. The powder α was obtained after washing with anhydrous ethanol and drying. After heat treatment at 750° C. under nitrogen for 2 hours, a black powder was obtained, which was the iron niobate / carbon composite material.
[0055] Embodiment 3:
[0056] (1) 1.2 mmol of terephthalic acid and 2.5 mmol of ferric chloride were added to 15 ml of N,N-2-methylformamide and stirred for 10 minutes to obtain solution A;
[0057] (2) The solution A obtained in step (1) was transferred to a 100 ml reactor and reacted at 110° C. for 20 hours, and then washed and dried with anhydrous ethanol to obtain a solution based on the central ion Fe 3+ MOFs precursor powder with terephthalic acid as ligand;
[0058] (3) 0.59 mmol of niobium acetate was dissolved in 35 ml of ethanol, and then 450 mg of the MOFs precursor in step (2) was added. After stirring and ultrasonicating for 20 minutes, the mixture was placed in a 100 ml reactor and reacted at 170° C. for 20 hours. The powder α was obtained after washing with anhydrous ethanol and drying. After heat treatment at 750° C. under nitrogen for 2 hours, a black powder was obtained, which was the iron niobate / carbon composite material.
[0059] Embodiment 4:
[0060] (1) 1.2 mmol of terephthalic acid and 2.5 mmol of ferric chloride were added to 15 ml of N,N-2-methylformamide and stirred for 10 minutes to obtain solution A;
[0061] (2) The solution A obtained in step (1) was transferred to a 100 ml reactor and reacted at 110° C. for 20 hours, and then washed and dried with anhydrous ethanol to obtain a solution based on the central ion Fe 3+ MOFs precursor powder with terephthalic acid as ligand;
[0062] (3) 0.2 mmol of niobium oxalate was dissolved in 35 ml of ethanol, and then 200 mg of the MOFs precursor in step (2) was added. After stirring and ultrasonication for 20 minutes, the mixture was placed in a 100 ml reactor and reacted at 170° C. for 20 hours. The powder α was obtained after washing with anhydrous ethanol and drying. After heat treatment at 750° C. under nitrogen for 2 hours, a black powder was obtained, which was the iron niobate / carbon composite material.
[0063] Embodiment 5:
[0064] (1) 2 mmol of terephthalic acid and 3.5 mmol of cobalt acetate were added to 15 ml of N,N-2-methylformamide and stirred for 10 minutes to obtain solution A;
[0065] (2) The solution A obtained in step (1) was transferred to a 100 ml reactor and reacted at 130° C. for 24 hours, and then washed and dried with anhydrous ethanol to obtain a central ion Co 2+ MOFs precursor powder with terephthalic acid as ligand;
[0066] (3) 0.3 mmol of niobium pentachloride was dissolved in 35 ml of ethanol, and then 200 mg of the MOFs precursor in step (2) was added. After stirring and ultrasonication for 20 minutes, the mixture was placed in a 100 ml reactor and reacted at 200° C. for 20 hours. The powder α was obtained after washing with anhydrous ethanol and drying. The powder was heat treated at 750° C. for 2 hours under nitrogen to obtain a black powder, which is a cobalt niobate / carbon composite material.
[0067] Embodiment 6:
[0068] (1) 1 mmol of terephthalic acid and 0.3 mmol of nickel nitrate were added to 15 ml of N,N-2-methylformamide and stirred for 10 minutes to obtain solution A;
[0069] (2) The solution A obtained in step (1) was transferred to a 100 ml reactor and reacted at 100° C. for 15 hours, and then washed and dried with anhydrous ethanol to obtain a Ni-based 2+ MOFs precursor powder with terephthalic acid as ligand;
[0070] (3) 0.2 mmol of niobium pentachloride was dissolved in 35 ml of ethanol, and then 200 mg of the MOFs precursor in step (2) was added. After stirring and ultrasonication for 20 minutes, the mixture was placed in a 100 ml reactor and reacted at 150° C. for 30 hours. The powder α was obtained after washing with anhydrous ethanol and drying. After heat treatment at 750° C. under nitrogen for 2 hours, a black powder was obtained, which was the nickel niobate / carbon composite material.
[0071] Comparative Example 1:
[0072] The difference from Example 1 is that in step (3), the powder α is not heat treated, that is, the black powder is not obtained after heat treatment at 750° C. for 2 hours under nitrogen. The rest is the same as in Example 1.
[0073] Comparative Example 2:
[0074] The difference from Example 1 is that the synthesis of the MOFs precursor in steps (1) and (2) is not performed, that is, 2 mmol of niobium pentachloride is directly dissolved in 35 ml of ethanol, and then 1 mmol of ferric chloride is added. After stirring and ultrasonication for 20 minutes, the mixture is placed in a 100 ml reactor and reacted at 200° C. for 24 hours. The powder α is obtained after washing with anhydrous ethanol and drying. After heat treatment at 750° C. for 2 hours under nitrogen, iron niobate powder is obtained.
[0075] Comparative Example 3:
[0076] The difference from Example 1 is that the temperature of heat-treating powder α in step (3) is changed, that is, black powder is obtained after heat treatment at 500° C. for 2 hours under nitrogen. The rest is the same as Example 1.
[0077] Comparative Example 4:
[0078] The difference from Example 1 is that the temperature of heat-treating powder α in step (3) is changed, that is, black powder is obtained after heat treatment at 1000° C. for 2 hours under nitrogen. The rest is the same as Example 1.
[0079] The niobate / carbon composite powder material obtained in step (3) of the above Examples 1 to 6 and Comparative Examples 1 to 4 was mixed with the conductive agent SuperP and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 7:2:1 to prepare a slurry, which was coated on the copper current collector, and a disc with a diameter of 1.2 cm was punched out as a lithium-ion battery electrode to assemble the battery. A microporous polypropylene membrane was used as a separator and 1 mol L -1 LiPF6 is used as the solute, ethylene carbonate (EC) and dimethyl carbonate (DMC) are used as the electrolyte with a volume ratio of 1:1 as the solvent, and the negative electrode lithium sheet is used to assemble the button battery. The charge and discharge voltage range is set to 3V-0.01V, and the assembled lithium-ion battery is subjected to constant current charge and discharge tests.
[0080] As the ratio and type of niobium salt and precursor MOFs change, the lithium-ion battery exhibits different electrochemical properties. After a niobate / carbon composite powder material in Examples 1-6 is assembled into a lithium-ion battery as a lithium-ion electrode material, its maximum discharge capacity at different current densities is shown in Table 1:
[0081] Table 1
[0082]
[0083]
[0084] It can be seen from Table 1 that when the feeding of niobium salt and MOFs is changed, reducing the ratio of niobium salt and MOFs causes the overall performance of the electrode material to decline, indicating that reducing the ratio of niobium salt and MOFs is not conducive to the formation of iron niobate, while increasing the ratio of niobium salt and MOFs makes the initial capacity of the electrode material better than that of Example 1, but the attenuation is more serious under high current. The reason may be that although increasing the ratio of niobium salt and MOFs is conducive to the formation of iron niobate, the accumulation of a large number of iron niobate particles leads to poor performance under high current; when the niobium source is changed, the material also shows good electrochemical properties (Example 4); and using cobalt acetate and nickel nitrate as metal salts for synthesizing precursor MOFs (Examples 5 and 6), the performance is not as good as that of Example 1 under high current, but it is still better than using traditional niobate electrodes.
[0085] From the comparison of the data of Examples 1 to 6 with Comparative Example 1, it can be seen that heat treatment is a necessary condition for forming MOFs-derived carbon and niobate. Omitting the heat treatment step will lead to a significant decrease in the performance of the final prepared material.
[0086] From the comparison of the data of Examples 1 to 6 and Comparative Example 2, it can be seen that MOFs as precursors are the basis for forming a carbon network. Omitting the preparation process of the MOFs precursor will lead to a significant decrease in the performance of the final prepared material.
[0087] From the data comparison of Examples 1 to 6 and Comparative Examples 3 and 4, it can be seen that the heat treatment temperature is the key condition for the formation of niobate and MOFs-derived carbon. If the treatment temperature is too low, it is not conducive to the formation of MOFs-derived carbon; if the treatment temperature is too high, the porous structure of niobate will be destroyed. Both of them lead to a significant decrease in the performance of the final prepared material.
[0088] Figure 4 The cycle performance diagram of the lithium ion battery in Example 1. It can be seen from the figure that the lithium ion battery has a current density of 1A g -1 The electrochemical performance was good, and it still maintained 240.6 mAh g after 280 cycles. -1 capacity. Figure 5 The rate diagram of the lithium ion battery in Example 1 is shown in Figure 2. The lithium ion battery is at 0.1, 0.2, 0.5, 1, and 2 A g -1 The maximum discharge capacities at current densities of 614.3, 242.2, 178.9, 125.8, and 71.1 mAh g -1 , showing good rate performance.
[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a niobate / carbon composite material, characterized in that: include: Adding terephthalic acid and metal salt into organic solvent A, mixing to obtain solution A, subjecting solution A to solvothermal reaction, and obtaining MOFs precursor powder; The niobium salt is dissolved in an organic solvent B, the MOFs precursor powder is added, and the mixture is mixed and subjected to a solvent thermal reaction to obtain a powder α, and the powder α is heat-treated to obtain a niobate / carbon composite material.
2. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The metal salt is at least one of cobalt acetate, cobalt nitrate, cobalt chloride, ferric chloride, ferric nitrate, ferric acetate, nickel acetate, nickel nitrate, and nickel chloride; The organic solvent A is at least one of N,N-2-methylformamide, diethylformamide and dimethyl sulfoxide.
3. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The dosage ratio of each component in the synthesis of the MOFs precursor powder is as follows: Organic solvent A 10-25ml; Terephthalic acid 1-2mmol; Metal salt 0.3-3.5mmol.
4. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The temperature of the solvothermal reaction of the solution A is 100-130° C. and the time is 15-24 hours.
5. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The niobium salt is at least one of niobium oxalate, niobium acetate and niobium chloride; The organic solvent B is at least one of ethanol and N,N-2-methylformamide.
6. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The dosage ratio of each component in the synthesis of the powder α is as follows: Organic solvent B 25-50ml; MOFs precursor powder 160-450 mg; Niobium salt 0.13-0.59mmol.
7. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The temperature of the solvent thermal reaction after the niobium salt and the MOFs precursor powder are mixed is 150-180° C. and the time is 20-30 hours.
8. The method for preparing a niobate / carbon composite material according to claim 1, characterized in that: The protective atmosphere of the heat-treated powder α is nitrogen or argon, the heat-treatment temperature is 600-900° C., and the time is 1-3 hours.
9. A niobate / carbon composite material prepared by the method according to any one of claims 1 to 8, characterized in that: The niobate / carbon composite material is a porous structure, and the niobate belongs to the orthorhombic crystal system.
10. Use of the niobate / carbon composite material as claimed in claim 9 as a negative electrode material for lithium-ion batteries.
Citation Information
Patent Citations
T-Nb2O5 / egg white carbon composite material used for lithium ion supercapacitor as well as preparation method thereof
CN109767925A
Calcium-based niobate compound potassium ion battery negative electrode material with frame structure and preparation method of calcium-based niobate compound potassium ion battery negative electrode material
CN111969197A
Titanium niobate / carbon composite electrode material and preparation method thereof
CN105552346A
Synthesis method for preparing carbon-coated CoTiO3 nanocrystalline material through MOF derivation
CN108666544A
Preparation method of lithium-rich ternary electrode material, product thereof and application thereof
CN109546146A